Channel estimation based on cyclic orthogonal training sequence for relay-assisted cooperative system - Zhi-peng ZHANG; Jie ZHONG; Min-jian ZHAO (Tongxin xuebao, 2012)
A practical channel estimation algorithm based on cyclic orthogonal training sequence for relay-assisted cooperative system was presented.According to this algorithm,the source node transmitted a cyclic orthogonal training sequence,and the relay nodes circularly shifted the received training sequences before retransmitted them.Although the relays retransmitted the training sequences to the destination node simultaneously,the correlation among them was fully eliminated.The corresponding least square (LS) and linear minimum mean square (LMMSE) channel estimators were derived.Simulation results confirm that the proposed algorithm has high accuracy,high efficiency and low complexity.